(3GdefUhQi aj GdWHs - (3eMeO Hf RcQjG GdnqQGRj, CHh HcQ,J (B311 (3g` s
(3BNQgG (B:s
(3hjMed Ydi GdfGQ hjhbO JMJg ef ZOhI Edi Gddjd ,dEEPG cGf ef GdZO Md GdWjf hNP eG aVd efg , hgh eGFd dhfg Edi GdUaQI hgh ef CLhO GdCOhjI s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B126s
(3fSNI QGHYIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B256 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs